Dipole instability in molecules irradiated by XUV pulses - Hughes, D.; Dundas, D.; Dinh, P. M.; Vincendon, M.; Reinhard, Paul-Gerhard; Suraud, E. (European Physical Journal D, 2023)
We study the response of small covalent molecules to XUV laser pulses. The theoretical description relies on a real-time and real-space Time-Dependent Density Functional Theory (TDDFT) approach at the level of the local density approximation complemented by an efficient self-interaction correction. We observe the development of a dipole instability well after the laser pulse has died out. We find that this instability mechanism is robust with respect to ionic motion, to a wide variety of laser characteristics and to the inclusion of incoherent correlations at the level of a relaxation time ansatz. To rule out any potential numerical effects, we use two independent computational implementations of the TDDFT approach. A comparison of the various laser parameters together with the widely used model approach consisting in an instantaneous hole excitation shows the generic character of this instability in terms of the level depletion of a deep lying electron state. An experimental verification of the phenomenon is proposed in terms of a time-resolved measurement of the photoelectron spectrum.
CRIS-Team Scopus Importer:2023-10-20